2011
DOI: 10.1902/jop.2010.100540
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cigarette Smoke Condensate and Nicotine on Human Gingival Fibroblast‐Mediated Collagen Degradation

Abstract: CSC may increase HGF-mediated collagen degradation by affecting membrane-associated MMPs and TIMPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 38 publications
2
39
0
1
Order By: Relevance
“…Similarly to the reports of other authors (6,15,25,27,41), in our study, the morphology of PDL fibroblasts and the fibril structure in the cell culture obtained from the nonsmoking patient were different from those observed in the smoking patient's sample. Concerning the attachment of cells on a surface, Peacock et al (29) demonstrated a positive effect of nicotine on gingival fibroblast attachment to a plastic surface and this enhanced effect was concentrationdependent.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly to the reports of other authors (6,15,25,27,41), in our study, the morphology of PDL fibroblasts and the fibril structure in the cell culture obtained from the nonsmoking patient were different from those observed in the smoking patient's sample. Concerning the attachment of cells on a surface, Peacock et al (29) demonstrated a positive effect of nicotine on gingival fibroblast attachment to a plastic surface and this enhanced effect was concentrationdependent.…”
Section: Resultssupporting
confidence: 79%
“…Cigarette smoking has been described as one of the most significant risk factors for the development and progression of periodontal diseases. In vitro studies have demonstrated nicotine to alter the cellular morphology and viability of cells derived from human periodontal tissue, as well as influence the ability of these cells to attach to a substrate and to synthesize extracellular matrix molecules (6,15,25,27,41). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As much as 85% of patients with acute MI were smokers compared to 42% in the SAP group. Tobacco smoking is one of the risk factors for both PD and CAD [15]. The lack of basic symptoms of periodontitis in smokers like edema and bleeding may mask development of infl ammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that oxidative stress mediated by H 2 O 2 was overcome by glutathione and recurred when nicotine was added, suggestive of a pro-oxidant role for nicotine [11]. Nicotine is also responsible for migration inhibition [4], cytoskeleton alteration [12], and extracellular matrix remodeling [13] in human gingival fibroblasts (HGFs), one of the cell types mostly exposed to smoking and vaping. There is documented evidence of the detrimental effects of nicotine on wound healing.…”
Section: Introductionmentioning
confidence: 99%